High definition lipomarking: Report of two patients - Manzaneda Cipriani, Raúl (2015)
We present the experience in liposuction, using lipo marking technique, standing out the natural shadows of abdominal contour, featuring an athletic person, performed in different areas of the abdominal wall, both in depth and surface, to get high definition of the abdominal contour. We report two cases: a 37 years old female, and a 40 years old male, who underwent surgery with this technique.